2011
DOI: 10.1029/2011gl047748
|View full text |Cite
|
Sign up to set email alerts
|

The pH dependence of spectral induced polarization of silica sands: Experiment and modeling

Abstract: 6p.International audienceIn electrolyte-saturated sands, the storage of electrical charges under an alternating electrical field (called "induced polarization") is responsible for a phase lag between the applied current and the resulting electrical field. Because a variety of polarization mechanisms exists in porous materials, the underlying physics of induced polarization is somehow unclear and the field data difficult to interpret quantitatively. Measurements at various pHs and salinities can be used to disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 16 publications
(38 reference statements)
2
61
0
Order By: Relevance
“…Equation 18 can be directly compared with equation 12. Skold et al (2011) recently presented an extension of this model that accounts for an additional polarization mechanism beyond the Stern layer polarization that these authors attribute to hopping of the protons on the mineral surface. This extension to the SLP model is used to explain the pH dependence of the imaginary conductivity observed for silica sands.…”
Section: The Slp Modelmentioning
confidence: 97%
See 2 more Smart Citations
“…Equation 18 can be directly compared with equation 12. Skold et al (2011) recently presented an extension of this model that accounts for an additional polarization mechanism beyond the Stern layer polarization that these authors attribute to hopping of the protons on the mineral surface. This extension to the SLP model is used to explain the pH dependence of the imaginary conductivity observed for silica sands.…”
Section: The Slp Modelmentioning
confidence: 97%
“…To account for this effect, Skold et al (2011) include an additional contribution to the specific surface conductivity,…”
Section: The Slp Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…However, hematite is much more conductive than goethite, so whereas hematite is likely to exhibit similar SIP behavior to magnetite, we predict that goethite will have a much smaller phase response that predominantly reflects pH dependent surface charge from iron hydroxyl groups, rather than the migration of mobile charges within the mineral itself. This dominant SIP polarization mechanism (related to polarization of an EDL defined by pH dependent surface charge) has previously been demonstrated by Skold et al (2011) for silica. We also note that surface charges might however be more important in field SIP measurements, where smaller iron (oxyhydr)oxide mineral particles and smaller applied voltage gradients than those used in this study may be present.…”
Section: And) ('mentioning
confidence: 99%
“…Previous workers have shown that the IP mechanisms can be very sensitive to changes in lithology and pore fluid chemistry (e.g., Pelton et al, 1978;Weller et al, 2010b;and Skold et al, 2011). Environmental examples for the successful use of SIP include the detection of clay units (e.g., Hördt et al, 2009;Attwa et al, 2011;and Attwa and Günther, 2012), the detection of both organic and inorganic contaminants (e.g., Olhoeft, 1984Olhoeft, , 1985Olhoeft, , 1992Chen et al, 2008Chen et al, , 2012andAbdel Aal et al, 2009, 2010) and hydraulic conductivity estimation (e.g., Tong and Tao, 2007).…”
Section: Introductionmentioning
confidence: 99%